Is motivation enough? Responsiveness, patient-centredness, medicalization and cost in family practice and conventional care settings in Thailand - Van Lerberghe Wim; Pongsupap Yongyuth (BMC, 2006)
Abstract Background In Thailand, family practice was developed primarily through a small number of self-styled family practitioners, who were dedicated to this professional field without having benefited from formal training in the specific techniques of family practice. In the context of a predominantly hospital-based health care system, much depends on their personal motivation and commitment to this area of medicine. The purpose of this paper is to compare the responsiveness, degree of patient-centredness, adequacy of therapeutic decisions and the cost of care in 37 such self-styled family practices, i.e. practices run by doctors who call themselves family practitioners, but have not been formally trained, and in 37 conventional public hospital outpatient departments (OPDs), 37 private clinics and 37 private hospital OPDs. Method Analysis of the characteristics of 148 taped consultations with simulated patients. Results The family practices performed better than public hospital OPDs with regard to responsiveness, patient-centredness and cost of technical investigations (M-W U: p < 0.001). Prescribing patterns were similar, but family practices prescribed fewer drugs and were less costly than private clinics and hospitals (M-W U: p < 0.001). The degree of patient-centredness was not significantly different. Private clinics and private hospitals scored better for responsiveness. Conclusion In Thailand self-styled family practices, even without specific training, provide a service that is more responsive and patient-centred than conventional care, with less overmedicalization and at a lower cost. Changes in prescription practices may require deeper changes in the medical culture.